A Compact Planar Monopole UWB MIMO Antenna for Short-Range Indoor Applications - Kolangiammal, Shanmugam; Balaji, Loganathan; Mahdal, Miroslav (Sensors (Basel, Switzerland), 2023)
A compact, four-element planar MIMO (Multiple Input, Multiple Output) antenna that operates in an ultra-wideband is presented for diversity application. The orthogonal position of the unit cells replicates the single antenna thrice, thereby decreasing mutual coupling. A UWB MIMO antenna measuring 35 × 35 × 1.6 mm3 is built using a microstrip line (50 Ω impedance) on an FR4 substrate having a thickness of 1.6 mm. The ground plane and radiator of this antenna are adjusted in several ways to bring it within its operating constraints between the frequencies of 3.1 GHz and 10.6 GHz. This technique makes the antenna small and covers the entire ultra-wideband (UWB) frequency range. The NI USRP was used to test the proposed MIMO antenna to determine its real-time performance. Based on the computed results, we conclude that this proposed antenna has outstanding characteristics in terms of performance and is suitable for wireless ultra-wideband indoor communication and diversity utilization with a small size.
Keywords: monopole; envelope correlation coefficient (ECC); directive gain; multiple input multiple output (MIMO); ultra-wideband antenna (UWB)